2012
DOI: 10.1021/nn3003778
|View full text |Cite
|
Sign up to set email alerts
|

Bulky Adamantanethiolate and Cyclohexanethiolate Ligands Favor Smaller Gold Nanoparticles with Altered Discrete Sizes

Abstract: Use of bulky ligands (BLs) in the synthesis of metal nanoparticles (NPs) gives smaller core sizes, sharpens the size distribution, and alters the discrete sizes. For BLs, the highly curved surface of small NPs may facilitate growth, but as the size increases and the surface flattens, NP growth may terminate when the ligand monolayer blocks BLs from transporting metal atoms to the NP core. Batches of thiolate-stabilized Au NPs were synthesized using equimolar amounts of 1-adamantanethiol (AdSH), cyclohexanethio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(124 citation statements)
references
References 97 publications
7
117
0
Order By: Relevance
“…They explained that during NP synthesis, steric overlapping of the voluminous ligands avoids the incorporation of more metal ions to the active surfaces of growing clusters, blocking the growth process and resulting in smaller NP sizes. 45 It is possible to infer from our results that a similar phenomenon occurred to the metal clusters attached to the protein nanotubes when GlcC 5 SH was used as coating compound.…”
Section: Synthesis Of Thiol-coated Gold Particles On Vp6 Nanotubes: Tsupporting
confidence: 55%
See 1 more Smart Citation
“…They explained that during NP synthesis, steric overlapping of the voluminous ligands avoids the incorporation of more metal ions to the active surfaces of growing clusters, blocking the growth process and resulting in smaller NP sizes. 45 It is possible to infer from our results that a similar phenomenon occurred to the metal clusters attached to the protein nanotubes when GlcC 5 SH was used as coating compound.…”
Section: Synthesis Of Thiol-coated Gold Particles On Vp6 Nanotubes: Tsupporting
confidence: 55%
“…It has also been demonstrated that bulkier ligands prevent the growth of gold clusters, limiting their size. 45 To test whether this phenomenon occurred in our system employing viral scaffolds in combination with thiols, the synthesis of Au NP was performed in the presence of β-D-glucopyranoside 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 10 (GlcC 5 SH), which has a larger size than MPS (Figure 3). This glyco-ligand can confer biocompatibility to gold nanocomplexes while avoiding their aggregation.…”
Section: Synthesis Of Thiol-coated Gold Particles On Vp6 Nanotubes: Tmentioning
confidence: 99%
“…Bulky ones, e.g. bearing an adamantane or carbohydrate backbone, are more efficient stabilizers and help stabilize MNPs of small sizes [85], [86]. .…”
Section: Influence Of Ligand Coordination At the Surface Of Metal Nanmentioning
confidence: 99%
“…This is consistent with previous studies showing that bulky thiol ligands resulted in smaller core sizes by comparison with nonbulky ligands. 66 It is likely that the C14 alkyl chains of L3 – L5 increase the volume of the NHC ligand close to the surface of the metallic core. This is particularly significant for L3 in which the intramolecular steric interactions between the long alkyl chains may lead to the largest ligand size (Figure 13).…”
Section: Synthesis Of Au Nanocrystals From Nhc-based Aui and Auiii Prmentioning
confidence: 99%